2022
DOI: 10.3390/v14071519
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Distribution, and Transmission of Alfalfa Viruses in China

Abstract: Alfalfa (Medicago sativa L.) is one of the most important quality forages worldwide and is cultivated throughout China. Alfalfa is susceptible to a variety of viral diseases during its growth, which has caused huge amounts of commercial losses. However, the profile of the alfalfa virus in China remains ambiguous and the viruses transmitted by Odontothrips loti (Haliday), dominant insect pests in alfalfa, are also poorly understood. In the present study, virus diversity was investigated in the primary alfalfa-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In China, AcCRaV and Actinidia virus 2 (AcV-2), both infecting kiwifruits, have been found in several provinces [52,54]. Further emaraviruses including JYMaV [55], PerMV [110], LiCRaV [62], Camellia chlorotic ringspot virus 1 (CaCRSV-1) and Camellia chlorotic ringspot virus 2 (CaCRSV-2) [59], PCLSaV [31], chrysanthemum mosaic-associated virus (ChMaV) [64,111], Japanese star anise ringspot-associated virus (JSARaV) [71], Vitis emaravirus (VEV) [67,68], alfalfa ringspot-associated virus (ARaV) [66], Ailanthus crinkle leaf-associated emaravirus (ACrLaV) [74] and PloAEV that infect important commercial fruits, ornamental crops and trees have been described in China and Japan. From other parts of the world there is limited information on emaraviruses diversity and distribution.…”
Section: Geographic Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…In China, AcCRaV and Actinidia virus 2 (AcV-2), both infecting kiwifruits, have been found in several provinces [52,54]. Further emaraviruses including JYMaV [55], PerMV [110], LiCRaV [62], Camellia chlorotic ringspot virus 1 (CaCRSV-1) and Camellia chlorotic ringspot virus 2 (CaCRSV-2) [59], PCLSaV [31], chrysanthemum mosaic-associated virus (ChMaV) [64,111], Japanese star anise ringspot-associated virus (JSARaV) [71], Vitis emaravirus (VEV) [67,68], alfalfa ringspot-associated virus (ARaV) [66], Ailanthus crinkle leaf-associated emaravirus (ACrLaV) [74] and PloAEV that infect important commercial fruits, ornamental crops and trees have been described in China and Japan. From other parts of the world there is limited information on emaraviruses diversity and distribution.…”
Section: Geographic Occurrencementioning
confidence: 99%
“…Beyond the four core segments, most emaraviruses possess additional genome segments. The only exceptions are PVBV [53], CjaV-2 [58], ARaV [65,66] and ACrLaV [74], however, overlooked segments might await discovery (see chapter 6.2.6). The number of additional segments differs considerably among species, from 1 for RYRaV to 6 for PerMV [61].…”
Section: Most Emaraviruses Encode Additional (Non-core) Genome Segmentsmentioning
confidence: 99%
“…Viral diseases are one of the most significant biological threats to alfalfa ( Medicago sativa ). Currently, more than 50 viral species have been reported that can infect alfalfa, causing severe symptoms such as enation, streak, yellowing, and mosaic, and inhibiting the normal growth and development of the alfalfa ( Han et al., 2019 ; Jiang et al., 2019 ; Li et al., 2021 ; Guo et al., 2022 ; Li et al., 2022 ). Viral diseases have become a vital factor hindering the development of the alfalfa industry.…”
Section: Introductionmentioning
confidence: 99%
“…At present, twenty-one species of alfalfa viruses have been detected in China ( Guo et al., 2022 ; Li et al., 2022 ). In our previous study, we found six viruses with a high incidence rate and virus loads in alfalfa were alfalfa mosaic virus (AMV), Medicago sativa alphapartitivirus 1 (MsAPV1), Medicago sativa alphapartitivirus 2 (MsAPV2), Medicago sativa deltapartitivirus 1 (MsDPV1), Medicago sativa amalgavirus 1 (MsAV1), and cnidium vein yellowing virus 1 (CnVYV1) ( Li et al., 2022 ). As a worldwide spread vital alfalfa virus that has drawn extensive attention, AMV may cause alfalfa biomass loss by up to 30% ( Han et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation